Syekh Muhammad Yasin Al-Fadani: Sang Penjaga Tradisi Sanad Keilmuan - Tetep Abdulatiep; Dadah Sa’adah; Ahmad Rifai (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to examine the role of Sheikh Muhammad Yasin Al-Fadani, an 'Alimul Riwayah who has written extensively on Sanad. The research method used is a qualitative approach with library research techniques where data is collected through written sources, both primary data derived from books written by Sheikh Al-Fadani and secondary data obtained from digitally based online sources. The analysis was conducted through an in-depth examination of Sheikh Al-Fadani's writings on Sanad and its role in the scientific tradition. The results of this study show that Sheikh Al-Fadani plays a very important role in maintaining and preserving the scientific tradition of sanad, especially in the field of hadith and other Islamic sciences. Through his detailed writings on the exposition and analysis of sanads, Sheikh Al-Fadani contributed to strengthening the scientific authority in the Islamic world, maintaining the authenticity and truthfulness of sanads, and ensuring the preservation of the scientific tradition passed down from generation to generation.